Light modulates oscillatory alpha activity in the occipital cortex of totally visually blind individuals with intact non-image-forming photoreception. Issue 1 (December 2018) - Vandewalle, Gilles; van Ackeren, Markus; Daneault, Véronique; Hull, Joseph; Albouy, Geneviève; Lepore, Franco; Doyon, Julien; Czeisler, Charles; Dumont, Marie; Carrier, Julie; Lockley, Steven; Collignon, Olivier
Abstract The discovery of intrinsically photosensitive retinal ganglion cells (ipRGCs) marked a major shift in our understanding of how light information is processed by the mammalian brain. These ipRGCs influence multiple functions not directly related to image formation such as circadian resetting and entrainment, pupil constriction, enhancement of alertness, as well as the modulation of cognition. More recently, it was demonstrated that ipRGCs may also contribute to basic visual functions. The impact of ipRGCs on visual function, independently of image forming photoreceptors, remains difficult to isolate, however, particularly in humans. We previously showed that exposure to intense monochromatic blue light (465 nm) induced non-conscious light perception in a forced choice task in three rare totally visually blind individuals without detectable rod and cone function, but who retained non-image-forming responses to light, very likely via ipRGCs. The neural foundation of such light perception in the absence of conscious vision is unknown, however. In this study, we characterized the brain activity of these three participants using electroencephalography (EEG), and demonstrate that unconsciously perceived light triggers an early and reliable transient desynchronization (i.e. decreased power) of the alpha EEG rhythm (8–14 Hz) over the occipital cortex. These results provide compelling insight into how ipRGC may contribute to transient changes in ongoing brain activity. They suggest that occipital alpha rhythm synchrony, which is typically linked to the visual system, is modulated by ipRGCs photoreception; a process that may contribute to the non-conscious light perception in those blind individuals.